Treatment and Outcomes of Thrombolysis Related Hemorrhagic Transformation: A Multi-Center Study in China - Liu, Junfeng; Wang, Yanan; Li, Jing; Zhang, Shanshan; Wu, Qian; Wei, Chenchen; Cui, Ting; Wu, Bo; Willey, Joshua Z.; Liu, Ming (Frontiers in Aging Neuroscience, 2022)
Objective: To investigate the current management of thrombolysis related HT in real-world practice, and whether these treatments would reduce the risk of 3-month death and hematoma expansion after HT. Methods: A multicenter retrospective study was performed in 3 comprehensive stroke centers in China (West China hospital, The First People’s Hospital of Ziyang, and Mianyang Central Hospital) between January 1st 2012 and December 31th 2020. Participants were patients diagnosed with HT after intravenous thrombolytics on brain CT within 36 hours after stroke onset. The treatment after thrombolysis related HT included aggressive therapy (procoagulant, neurosurgical treatment) and dehydration therapy (mannitol or glycerin and fructose). The primary clinical outcome was 3-month death. The primary radiographic outcome was hematoma expansion, defined as a 33% increase in the hematoma volume using the (A × B × C)/2 method on follow-up imaging. Results: Of 538 patients with ischemic stroke receiving thrombolysis included during the study period, 94 patients (17.4%) were diagnosed with HT, 50% (47/94) of whom were symptomatic HT. The 3-month death was 31.5% (29/92), with 2 patients having been lost to follow up. 68 patients (72.3%) had follow-up brain CT scans after HT detection for evaluating hematoma expansion, of whom 14.7% (10/68) had hematoma expansion. Among the 10 patients with hematoma expansion, 7 patients were from symptomatic HT group and 3 patients were from the asymptomatic hematoma group. In regard to escalation in therapy, 6 patients received neurosurgical treatment and 3 patients had a fresh frozen plasma infusion. In addition, dehydration therapy was the most common management after HT diagnosis (87.2% [82 of 94]). In the multivariable models, refusing any treatment after HT diagnosis was the sole factor associated with increased 3-month death (odds ratio, 13.6; 95% CI, 3.98–56.9) and hematoma expansion risk (odds ratio, 8.54; 95% CI, 1.33–70.1). Conclusions: Refusing any treatment after HT detection had a significant trend of increasing 3-month death and hematoma expansion risk after HT. Our finding of hematoma expansion among patients with asymptomatic HT in non-western populations suggests an opportunity for intervention.